1972
DOI: 10.1159/000114429
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Parkinson’s Disease with Amantadine and L-Dopa

Abstract: Treatment of Parkinson’s disease with amantadine and L-dopa was studied in 82 patients. A double-blind cross-over trial with 38 patients showed a significant benefit with 200 mg of amantadine daily. During non-blind treatment with 300 mg of amantadine for 2–4 months 60% of the patients showed moderate or marked overall improvement. The results were independent of age, sex, duration or severity of the disease or previous thalamotomy. During combined treatment an additive effect of L-dopa, but not that of amanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…AMH was originally used as an antiviral agent for influenza type A. Subsequent studies showed it to be effective in treating PD and multiple sclerosis (Godwin-Austen et al, 1970; Rinne et al, 1972; Cohen and Fisher, 1989). Though the mechanism of action for AMH treatment of PD and multiple sclerosis is not completely understood, biochemical studies have demonstrated that AMH increases extracellular DA concentrations by blocking reuptake and by facilitating the synthesis of DA (Von Voigtlander and Moore, 1971; Bak et al, 1972; Gianutsos et al, 1985).…”
Section: Dopamine In the Clinic: The Past And Future Role Of Da Agmentioning
confidence: 99%
“…AMH was originally used as an antiviral agent for influenza type A. Subsequent studies showed it to be effective in treating PD and multiple sclerosis (Godwin-Austen et al, 1970; Rinne et al, 1972; Cohen and Fisher, 1989). Though the mechanism of action for AMH treatment of PD and multiple sclerosis is not completely understood, biochemical studies have demonstrated that AMH increases extracellular DA concentrations by blocking reuptake and by facilitating the synthesis of DA (Von Voigtlander and Moore, 1971; Bak et al, 1972; Gianutsos et al, 1985).…”
Section: Dopamine In the Clinic: The Past And Future Role Of Da Agmentioning
confidence: 99%
“…This study had a quality rating score of 55%. Rinne et al (1972) 26 performed a double-blind, non-randomized, placebo-controlled, crossover study of 4 weeks duration. The efficacy of amantadine versus placebo was compared in 38 patients with PD receiving anticholinergic therapy.…”
Section: Adjunct Therapy Amantadine As Adjunct To Anticholinergic Thementioning
confidence: 99%
“…Corresponding analyses were made afLer administration of amantadine, because it has been reported to have a beneficial effect in some parkinsonian cases (Schwab et aI., 1969;Godwin-Austen et al, 1970;Hunter et aL, 1970;Rinne et al, 1972). Since &anges in the concentration of plasma insulin and blood sugar effectively regulate the secretion of growth hormone, particular attention has been paid to these factors.…”
Section: Introductionmentioning
confidence: 99%